Nationwide Assessment of Knowledge and Perception in Reinforcing Telemedicine in the Age of COVID-19 Among Medical Students From Pakistan - Sana Kazmi; Farah Yasmin; Sarush Ahmed Siddiqui; Muzhgan Shah; Rabbia Tariq; Hamza Nauman; Usama Saeed; Amir Hassan; Muhammad Sohaib Asghar; Tooba Hussain (Frontiers Media S.A., 2022)
The urgency for telemedicine is felt during the COVID-19 pandemic which has rendered the world shut by enforcing quarantines and lockdowns. Many developing countries including Pakistan have inadequate telehealth care services that limited access to rural and remote areas. A cross-sectional survey was carried out among medical students i.e., both preclinical and clinical enrolled in various medical colleges from all provinces of Pakistan to determine their Knowledge, Attitude and Perception regarding the use of Telemedicine during the COVID-19 Pandemic. A total of 398 respondents were included in this preliminary survey. Knowledgeable scores were calculated, from a maximum obtainable score of 7. The mean knowledge was found to be significantly associated with age, province, and year of study (p-value < 0.05). Attitude scores were calculated from a maximum obtainable score of 10. All the independent variables failed to reach a significant (p < 0.05) association with the mean attitude of respondents about telemedicine. Perception scores were calculated from a maximum obtainable score of 8. Residents of Khyber Pakhtunkhwa are more likely to know about telemedicine than Balochistan (p = 0.022) on univariate regression. We identified, lack of knowledge and training for telemedicine in medical institutes. It is crucial to assess the knowledge of medical students regarding telemedicine to comprehend, and evaluate their attitude as future doctors who can play a significant role in establishing telemedicine services in the health care system.